Chilling injury as an indicator of critical temperature for cold storage of guava (Psidium guajava L.) cv. Allahabad Safeda. (12th December 2006) - Tiwari, Suresh; Tandon, D.K.; Esguerra, Elda B.
The critical temperature for cold storage of guava cutivar Allahabad Safeda and the changes in physico-chemical attributes during its storage were studied. Fruits were stored at 5, 8 and 15° C with 85–90% relative humidity and withdrawn weekly from cold storage and kept at ambient condition (18–20° C and 65–70% RH) for analysis. Chilling Injury (CI) symptoms, characterised by browning of peel, development of pitting on fruit surface and desiccation of fruit, appeared after 2 weeks in the fruits stored at 5° C. These symptoms became more aggravated when the storage at ambient condition prolonged upto 6 days and when the fruits did not ripen uniformly. The CI symptoms in the fruits stored at 5° C showed membrane damage, i.e. higher electrolyte leakage values and low ethylene levels. However, the fruits stored at 8 and 15° C did not exhibit any symptoms of CI and ripened well until 3 weeks of cold storage.